2015
DOI: 10.1177/0363546514562174
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Management of Osteochondritis Dissecans Lesions of the Patella and Trochlea in the Pediatric and Adolescent Population

Abstract: Surgical treatment of patellofemoral OCD in children and adolescents produces a high rate of satisfaction and return to sports. Female sex, prolonged duration of symptoms, and internal fixation may be associated with worse outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 44 publications
(68 reference statements)
1
72
0
1
Order By: Relevance
“…c After osteochondral plugs implantation To date, no study on the treatment of OCDP by autologous osteochondral mosaicplasty in children has been published. Rare series are reported in the literature concerning the management of OCDP in children and adolescents using the conventional techniques [10,24]. Resection of the osteochondral fragment followed by perforation [9] or curettage [8,10] of the subchondral bone often results in poor outcomes [8,25].…”
Section: Discussionmentioning
confidence: 99%
“…c After osteochondral plugs implantation To date, no study on the treatment of OCDP by autologous osteochondral mosaicplasty in children has been published. Rare series are reported in the literature concerning the management of OCDP in children and adolescents using the conventional techniques [10,24]. Resection of the osteochondral fragment followed by perforation [9] or curettage [8,10] of the subchondral bone often results in poor outcomes [8,25].…”
Section: Discussionmentioning
confidence: 99%
“…MRI allows axial imaging of the patellofemoral joint with the knee in full extension, allowing better characterization and localization of patellofemoral chondral defects and aids in evaluation of the subchondral bone. 6,[21][22][23][24] In select patients, computed tomography arthrogram may improve the definition of the lesion.…”
Section: Preoperative Planning and Considerationsmentioning
confidence: 99%
“…Studies have shown success with fixation of these lesions in both skeletally immature and mature populations, using both metal and bioabsorbable screws, but careful preoperative evaluation of imaging and individual patient factors should be fully assessed. [6][7][8]25,26 Hardware prominence, loss of fixation, and screw breakage are frequently reported complications resulting from internal fixation of OCD lesions. 6,27,28 Preoperative assessment of lesion size, overall patella size and depth, available subchondral bone, and implant choice should all be considered.…”
Section: Preoperative Planning and Considerationsmentioning
confidence: 99%
See 2 more Smart Citations